Pengaruh Religiusitas, Pelayanan Fiskus dan Sanksi Pajak pada Kepatuhan Wajib Pajak Orang Pribadi - Dwi Purwadi, Made Okvan; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p30, 2019)
Increased tax revenue is based on several important factors, one of which is tax compliance. Religiosity, tax services and tax sanctions are some of the factors that influence tax compliance. Knowing the influence between religiosity, tax authorities, and tax sanctions on individual taxpayer compliance is the aim of this study, with the South Badung KPP as the research location. Determined as many as 100 respondents who are WPOPs registered at KPP Pratama Badung as the research sample. Samples were determined by convenience sampling method and data obtained were analyzed using multiple linear regression analysis. Based on the results of the study it was found that religiosity, tax authorities services, and tax sanctions each had a positive influence on individual taxpayer compliance at the South Badung Tax Office. Keywords : Religiosity, ministry of fiscal, tax sanctions, taxpayer compliance.